2014
DOI: 10.5301/ejo.5000525
|View full text |Cite
|
Sign up to set email alerts
|

Change in Tear Film Characteristics in Visual Display Terminal Users

Abstract: Both symptoms and signs of dry eye increased significantly with computer use. Approximately 1 of every 3-4 computer users was found to have dry eye with higher tear osmolarity values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 27 publications
5
94
1
1
Order By: Relevance
“…14 TBUT was significantly increased in the computer users as compared to nonusers which is in accordance with various studies by Yagizi et al, Bhargava et al and Unlo et al 9,10,13 In the current study slit lamp based TMH was significantly higher in computer users as compared to non users which is quite contradictory but can be explained by the fact that slit lamp bright light can lead to reflex tearing. Pallikaru et al hypothesized that the increase in tear meniscus volume was compensated by an increase in output resulting from blinking.…”
Section: Discussionsupporting
confidence: 90%
“…14 TBUT was significantly increased in the computer users as compared to nonusers which is in accordance with various studies by Yagizi et al, Bhargava et al and Unlo et al 9,10,13 In the current study slit lamp based TMH was significantly higher in computer users as compared to non users which is quite contradictory but can be explained by the fact that slit lamp bright light can lead to reflex tearing. Pallikaru et al hypothesized that the increase in tear meniscus volume was compensated by an increase in output resulting from blinking.…”
Section: Discussionsupporting
confidence: 90%
“…In the study by Nakamura et al of office workers in Japan, a decreased Schirmer score was evident for those working on computers for longer than two hours per day or for more than four years of use. Reduced Schirmer scores have been reported after a nine‐hour day in computer users compared to non‐computer users (janitors) and in a study of female habitual computer users compared to female workers in the same offices who were not computer users . Reduced tear meniscus height was similarly reported after 20 minutes of playing a computer game when compared to viewing of a distant object, but the tear meniscus height did not vary between a slow‐paced and a fast‐paced game …”
Section: Blinking Tear Function and Dry Eyementioning
confidence: 94%
“…Reduced tear break‐up time occurs with computer use . Reduced tear break‐up time and lipid layer thickness have been shown after as little as 20 and 60 minutes of playing a computer game (both slow‐paced and fast‐paced), although an earlier study did not find a difference in tear break‐up time after 10 minutes .…”
Section: Blinking Tear Function and Dry Eyementioning
confidence: 95%
“…Up to 27.4% of VDU users reportedly have high tear osmolarity levels [613]. Kojima et al [614] reported that long-term VDU users (using digital devices more than 4 h per day) exhibited a significantly reduced TMH and increased symptom scores compared to short-term VDU users and controls.…”
Section: Non-pathophysiological Factors Impacting the Tear Filmmentioning
confidence: 99%